Promoting learner autonomy through EFL textbook: the textbook facilitation and the students’ and teacher’s perceptions - M. Ibnu Mustofa; Yanty Wirza (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2023)
Studies on learner autonomy (LA) in EFL learning have been widely reported. However, the promotion of LA through EFL textbooks in Indonesia remains under-explored. This study investigated the extent to which the EFL textbook Erlangga Straight Point Series (ESPS) facilitates LA, the students’ perceptions of the textbook in promoting LA, and the teacher's perceptions of LA facilitation in the textbook contributing to EFL learning. This study employed quantitative and qualitative research designs involving 20 EFL students and an EFL teacher at a private Islamic senior high school in Bengkulu, Indonesia. The data were garnered from the textbook evaluation, the student questionnaires, and the teacher interview. The corpus data were analyzed through the framework by Nunan (1997), the questionnaires were through percentage calculation, and the interview results were through thematic analysis. The results showed that LA is not optimally facilitated in task sections of the textbook. Moreover, the students perceived the textbook only supported LA through the principles of classroom activities, self-assessment, and self-reflection. Meanwhile, the teacher positively perceives LA, but institutional support for its implementation is unavailable. This study implies the pivotal roles of all stakeholders in education to support autonomous learners through EFL textbooks.